EVALUATION OF DERVIS HASAN MEHDI’S ARTWORK TITLED TERCUME-I ŞÂHNÂME-I FIRDEVSÎ ON TERMS OF THE TURKISH ART WORKS - Ruhi KONAK (Fırat University, 2020)
Considered as one of the important works of Persian literature, Şehname, which deals with heroic and epic events, is one of the most known and read works of the Islamic world. Many copies of the book, which was written by Firdevsi in Iran, are decorated and numerous subjects described in the text are illustrated. In this respect, the Firedevsi Şehname, which has the feature of a valuable book, was read by Ottoman rulers with pleasure and for hide it in their libraries. During the developing period, while some Ottoman Sultans were preparing their ancestors or their own Şehnames, who made the translation of the Firedevsi Şehname too. New sections were added to these translated works in line with the appreciation of the Sultan who had prepared the book. Thus, the book, which became the Shahnameh of the related Ottoman Sultan, became an intermediary for the Sultan to explain himself or mention him. The Şehname that can look at the examples that come to our day, has an important place in terms of book arts as well as being a literary work. There are both the copies made by other authors, the copies made by other names, and translations of the original work in your library, museum and private collections at home and abroad. Tercüme-i Şâhnâme-i Firdevsî is located in Paris Bibliotheque Nationale. This work, in which there are examples of skin, marbling, painting and illumination art, was examined from the point of view of Ottoman book arts within the scope of the study. The volume, gilding, illumination, marbling and painting examples in the work, in terms of period, style features and artist samples were examined.